Adeno-associated virus–targeted disruption of the CFTR gene in cloned ferrets - Sun, Xingshen (American Society for Clinical Investigation, 2008)

(untitled)
Somatic cell gene targeting combined with nuclear transfer cloning presents tremendous potential for the creation of new, large-animal models of human diseases. Mouse disease models often fail to reproduce human phenotypes, underscoring the need for the generation and study of alternative disease models. Mice deficient for CFTR have been poor models for cystic fibrosis (CF), lacking many aspects of human CF lung disease. In this study, we describe the production of a CFTR gene–deficient model in the domestic ferret using recombinant adeno-associated virus–mediated gene targeting in fibroblasts, followed by nuclear transfer cloning. As part of this approach, we developed a somatic cell rejuvenation protocol using serial nuclear transfer to produce live CFTR-deficient clones from senescent gene-targeted fibroblasts. We transferred 472 reconstructed embryos into 11 recipient jills and obtained 8 healthy male ferret clones heterozygous for a disruption in exon 10 of the CFTR gene. To our knowledge, this study represents the first description of genetically engineered ferrets and describes an approach that may be of substantial utility in modeling not only CF, but also other genetic diseases.